PRC2 Is Dispensable in Vivo for β-Catenin-Mediated Repression of Chondrogenesis in the Mouse Embryonic Cranial Mesenchyme. Issue 2 (1st February 2018) - Ferguson, James; Devarajan, Mahima; DiNuoscio, Gregg; Saiakhova, Alina; Liu, Chia-Feng; Lefebvre, Veronique; Scacheri, Peter C; Atit, Radhika P
Abstract: A hallmark of craniofacial development is the differentiation of multiple cell lineages in close proximity to one another. The mouse skull bones and overlying dermis are derived from the cranial mesenchyme (CM). Cell fate selection of the embryonic cranial bone and dermis in the CM requires Wnt/β-catenin signaling, and loss of β-catenin leads to an ectopic chondrogenic cell fate switch. The mechanism by which Wnt/β-catenin activity suppresses the cartilage fate is unclear. Upon conditional deletion of β-catenin in the CM, several key determinants of the cartilage differentiation program, including Sox9, become differentially expressed. Many of these differentially expressed genes are known targets of the Polycomb Repressive Complex 2 (PRC2). Thus, we hypothesized that PRC2 is required for Wnt/β-catenin-mediated repression of chondrogenesis in the embryonic CM. We find that β-catenin can physically interact with PRC2 components in the CM in vivo . However, upon genetic deletion of Enhancer of Zeste homolog 2 (EZH2), the catalytic component of PRC2, chondrogenesis remains repressed and the bone and dermis cell fate is preserved in the CM. Furthermore, loss of β-catenin does not alter either the H3K27me3 enrichment levels genome-wide or on cartilage differentiation determinants, including Sox9 . Our results indicate that EZH2 is not required to repress chondrogenesis in the CM downstream of Wnt/β-catenin signaling.